Experimental and comparison study on heat and moisture transfer characteristics of desiccant coated heat exchanger with variable structure sizes. (5th June 2018) - Sun, X.Y.; Dai, Y.J.; Ge, T.S.; Zhao, Y.; Wang, R.Z.
Highlights: Three types of novel DCHEs with variable structure sizes are tested and compared. Ranks of influence factors in experiments are obtained by using Taguchi method. Higher surface compactness of DCHE means higher heat and mass transfer capacity. Heat and mass transfer coefficients are functions of pressure drop. Abstract: Desiccant-coated heat exchanger (DCHE) is a novel component for handling both sensible and latent heat assisted by desiccant materials. In this paper, three types of DCHEs with the same transfer surface area, DCHE A (fin pitch 2 mm, fin depth 44 mm), DCHE B (fin pitch 3 mm, fin depth 66 mm) and DCHE C (fin pitch 4 mm, fin depth 88 mm), are fabricated to make out the relationships between structure sizes and performance characteristics. The transient heat and moisture transfer performance, as well as the pressure drop passing through DCHEs, are tested and compared in depth. By using Taguchi method, the ranks of influence factors in heat and mass transfer performances are obtained. With the same transfer surface area but different surface compactness, three DCHEs show different heat and mass transfer capacities and different pressure drops. DCHE A with the highest surface compactness shows the highest heat and mass transfer capacity, while the highest pressure drop is shown as deficiency. DCHE C with the smallest surface compactness shows the highest heat recovery efficiency and the lowest pressure drop. Heat transfer coefficient of DCHE A is 14.9% greater than DCHE B, 19.6% greater than DCHE C in dehumidification process. The moisture adsorbed value of DCHE A is 9.6% greater than DCHE B, 18.2% greater than DCHE C. Pressure drop of DCHE A is 50% larger than DCHE B, and 90% larger than DCHE C. The correlations of Nusselt number and Euler number of three DCHEs are summarized by fitting the experimental data.